Characteristics and metal leachability of incinerated sewage sludge ash and air pollution control residues from Hong Kong evaluated by different methods. (June 2017) - Li, Jiang-shan; Xue, Qiang; Fang, Le; Poon, Chi Sun
Graphical abstract: Highlights: Six methods were used to investigate the metals leachability of ISSA and APCR. A low leaching rate of metals although high concentrations of Zn and Cu. Metals solubilization occurred mainly due to acid attack. ISSA had more irregularly shaped particles with a larger size than APCR. ISSA and APCR could be used as fine aggregate or filler aggregate. Abstract: The improper disposal of incinerated sewage sludge ash (ISSA) and air pollution control residues (APCR) from sewage sludge incinerators has become an environmental concern. The physicochemical, morphological and mineralogical characteristics of ISSA and APCR from Hong Kong, and the leachability and risk of heavy metals, are presented in this paper. The results showed that a low hydraulic and pozzolanic potential was associated with the ISSA and APCR due to the presence of low contents of SiO2, Al2 O3 and CaO and high contents of P, S and Cl (especially for APCR). Although high concentrations of Zn and Cu (especially for ISSA) followed by Ni, Pb and As, Se were detected, a low leaching rate of these metals (especially at neutral and alkaline pH) rendered them classifiable as non-hazardous according to the U.S. EPA and Chinese national regulatory limits. The leached metals concentrations from ISSA and APCR were mainly pH dependent, and metals solubilization occurred mainly at low pH. Different leaching tests should be adopted based on the simulated different environmental conditions and exposure scenarios for assessing the leachability as contrasting results could be obtained due to the differences in complexing abilities and final pH of the leaching solutions.